Structure formation in multi-layer forgings from carbon and corrosion-resistant steel and copper alloys - Myronova , T.M.; Ashkelianets , A.V.; Bondarev , S.V.; Guba , R.M. (Theory and Practice of Metallurgy, 2024)
The development of the technology for obtaining multi-layer forgings from various alloys contributes to the saving of scarce materials such as chrome-nickel corrosion-resistant steels. The properties of multilayer products combine the strength of the main layer of structural steel and the increased corrosion resistance of the highly alloyed layer, which is in direct contact with the working environment. Multi-layer materials are used in various industries. Laminated steel or laminate is used as a different tool. Laminate is a central sheet (plate), covered on both sides with sheets of steel of a different grade. The laminate tool has improved characteristics, it combines the properties of the central sheet and covers. One of the most common methods of manufacturing such materials is hot deformation. The most important problem in the production of multilayer steel composites is to ensure high-quality welding between layers of different steels. To develop the mode of forging multilayer blanks, computer modeling was carried out in the QForm program. After obtaining the simulation results, the heating modes were determined and the forging of composite packages from different steels was carried out. Deformation of the experimental samples was carried out by forging broach. After calculating the forging parameters, two passes were taken to deform the workpiece with a total degree of forging of 2.56. The following alloys were used for multilayer packages to be forged: for the central layer of ShH15, St 3 steel, for the covers AISI321 steel, which is an analogue of 08X18H10T steel, for intermediate layers - M1 copper and L63 brass. The peculiarities of the microstructure in the zones of contact welding of layers of brass - carbon steel and brass steel AISI321, copper - carbon steel, copper - steel AISI321, copper steel ShH15 were studied. As an intermediate layer for better welding of steel layers to each other in the forging process, as well as to prevent the diffusion of carbon and alloying elements, it is appropriate to recommend the use of M1 copper plate.